Drug Burden Index to Define the Burden of Medicines in Older Adults with Intellectual Disabilities: An Observational Cross-Sectional Study - Mc Carron, Mary; O'Connell, Juliette Anne; O'Dwyer, Maire; Burke, Eilish; O'Connell, Juliette; Henman, Martin (My University, 2018)
Aims: The drug burden index (DBI) is a dose‐related measure of anticholinergic and sedative drug exposure. This cross‐sectional study described DBI in older adults with intellectual disabilities (ID) and the most frequently reported therapeutic classes contributing to DBI and examined associations between higher DBI scores and potential adverse effects as well as physical function. Methods: This study analysed data from Wave 2 (2013/2014) of the Intellectual Disability Supplement to the Irish Longitudinal Study on Ageing (IDS‐TILDA), a representative study on the ageing of people with ID in Ireland. Self‐ and objectively‐reported data were collected on medication use and physical health, including health conditions. The Barthel index was the physical function measure. Results: The study examined 677 individuals with ID, of whom 644 (95.1%) reported taking medication and 78.6% (n = 532) were exposed to medication with anticholinergic and/or sedative activity. 54.2% (n = 367) were exposed to high DBI score (≥1). Adjusted multivariate regression analysis revealed no significant association between DBI score and daytime dozing, constipation or falls. After adjusting for confounders (sex, age, level of ID, comorbidities, behaviours that challenge, history of falls), DBI was associated with significantly higher dependence in the Barthel index (P = 0.002). Conclusions: This is the first time DBI has been described in older adults with ID. Scores were much higher than those observed in the general population and higher scores were associated with higher dependence in Barthel index activities of daily living.
PUBLISHED
Keywords: Ageing; Drug utilization; Pharmacoepidemiology; Ageing; Inclusive Society; ANTICONVULSANT DRUGS; ANTIDEPRESSANT DRUGS; ANTIEPILEPTIC DRUGS; ANTIPSYCHOTIC DRUGS; ATYPICAL ANTIPSYCHOTIC-DRUGS; Ageing & Intellectual Disability Issues; Ageing, Health and Intellectual Disability; Aging and Intellectual Disability; Clinical Pharmacy; DRUGS, EFFECTS; Intellectual Disability; MEDICATION; MEDICATION MANAGEMENT; MEDICATION REVIEW; MEDICATION USE; MEDICATIONS; Medication Reconciliation; Medication burden; Medication safety; Medicines; Mental health and intellectual disability; NEUROLEPTIC MEDICATION; PHARMACEUTICAL CARE; PHARMACY PRACTICE; POLYPHARMACY; PSYCHOTROPIC; Pharmaceutical Policy; Pharmaceutical care of the elderly; Pharmacy; Pharmacy Research; Practice of pharmacy; Prescription Medicines; Psychotropic medication; QUALITY USE OF MEDICINES; anticholinergic medication; Age-related disability; Autistic Spectrum disorders; Chronic Health Condition; Emotional-behavioural Problems; Epilepsy; Intellectual Disability; Mental Health/Psychosocial disability; Physical disability; Health